2015
DOI: 10.1038/srep08043
|View full text |Cite
|
Sign up to set email alerts
|

Multi-trait mimicry of ants by a parasitoid wasp

Abstract: Many animals avoid attack from predators through toxicity or the emission of repellent chemicals. Defensive mimicry has evolved in many species to deceive shared predators, for instance through colouration and other morphological adaptations, but mimicry hardly ever seems to involve multi-trait similarities. Here we report on a wingless parasitoid wasp that exhibits a full spectrum of traits mimicing ants and affording protection against ground-dwelling predators (wolf spiders). In body size, morphology and mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…Furthermore, a recent study by Malcicka et al . () found that wingless facultative hyperparasitoids in the genus Gelis (Hymenoptera: Ichneumonidae) exhibited a suite of traits – morphological, behavioural, and chemical – that mimic ants, especially the black garden ant, Lasius niger L. Chemical mimicry of ant communication pheromones by Gelis agilis (F.) expressed as alarm pheromones when threatened greatly reduces the risk of predation by cursorial wolf spiders. Another good example of specialism related to phagy is the deployment of specific behaviour by some parasitic flies, for example the bot fly of South America, Dermatobia hominis (L. Jr.) (Diptera: Cuterebridae), when parasitizing large mammals, including cattle and occasionally humans.…”
Section: Examples Of Insect Specialismsmentioning
confidence: 99%
“…Furthermore, a recent study by Malcicka et al . () found that wingless facultative hyperparasitoids in the genus Gelis (Hymenoptera: Ichneumonidae) exhibited a suite of traits – morphological, behavioural, and chemical – that mimic ants, especially the black garden ant, Lasius niger L. Chemical mimicry of ant communication pheromones by Gelis agilis (F.) expressed as alarm pheromones when threatened greatly reduces the risk of predation by cursorial wolf spiders. Another good example of specialism related to phagy is the deployment of specific behaviour by some parasitic flies, for example the bot fly of South America, Dermatobia hominis (L. Jr.) (Diptera: Cuterebridae), when parasitizing large mammals, including cattle and occasionally humans.…”
Section: Examples Of Insect Specialismsmentioning
confidence: 99%
“…Gauld (1987) has suggested three possible advantages of nocturnal foraging of parasitoid wasps: (1) escape from diurnal predators, (2) access to nocturnal hosts, and (3) avoidance of high temperatures and drying in sunlight. Predation of small wasps such as Meteorus by hunting spiders is probably common enough to serve as a selective force for evolution of mimicry in parasitoids (Malcicka et al 2015), but many wolf spiders are nocturnal rather than diurnal according to Suter (2014). Thus, their forces on the daily activity pattern of prey parasitoids seem limited, if any.…”
Section: Discussionmentioning
confidence: 98%
“…Mass spectrometer was run in scan mode in the mass range m/z 33 to 350. For identification of sulcatone (6-methyl-5-hepten-2-one) the mass spectrum of the peak with a retention time of ~8.2 min was compared to the entry of sulcatone in the commercially available Wiley mass spectra library (see also methods for identification of sulcatone in Malcicka et al 2015 ). Moreover, spectral comparisons with published literature indicated a consistency with sulcatone.…”
Section: Methodsmentioning
confidence: 99%
“…Many Gelis species are wingless and closely resemble ants morphologically and even chemically. For example, Malcicka et al ( 2015 ) found that Gelis agilis Fabricius (Hymenoptera: Ichneumonidae, Cryptinae) closely resembles the common black ant Lasius fuliginosus Latreille (Hymenoptera: Formicidae) in terms of general body shape and size, color and also defensive chemistry. When agitated, both G. agilis and L. fuliginosus secrete 6-methyl-5-hepten-2-one (sulcatone) that functions as an alarm/panic pheromone.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation